Alloyability of warm formed FeCrAl powder compacts. (September 2015) - Rahman, M.M.; Talib, A.A.A.
Abstract: Alloyability of warm formed Fe-based powder compacts is presented here. Iron (Fe) powder ASC100.29 was mixed with other alloying elements, namely chromium (Cr), and aluminum (Al) powder for 60 min and compacted at 150 °C by applying 130 kN axial loading, simultaneously from upper and lower punches to generate green compacts. The defect-free green compacts were subsequently sintered in argon gas fired furnace at 800 °C for three different holding times, i.e., 30, 60, and 90 min. Sintered samples were then analyzed through XRD and SEM/EDX for their alloyability. The results from XRD and SEM/EDX such as peak, intensity, microstructure, and element spectrum were studied. The flexure stress of the sintered samples was also measured to relate with their alloyability. The results revealed that the alloyability and microstructures of sintered products were affected by sintering time. The sample sintered for 60 min showed the highest intensity of FeCrAl alloy and bending strength.